المناسبات بين السور في "التيسير في التفسير" لأبي حفص النسفي: The Correlation Between Surah in "Al-Taysir Fi Al-Tafsir" by Abu Hafs Al-Nasafi - Mutashim Billah Suharnawan; Muhammad bin Abdullah bin Sulaiman Aba al-Khail (البصيرة: مجلة الدراسات الإسلامية, 2025)
Hafs al-Nasafi's "Al-Taysir fi al-Tafsir", a critical aspect of Qur'anic studies that highlights the coherence and wisdom of Surah arrangement. The study aims to analyze al-Nasafi's methodology in presenting these correlations, their types, and the connecting elements he employed, show casing his contributions to understanding inter-Surah harmony. The research utilized the inductive method to collect relevant data and the descriptive method to analyze al-Nasafi’s approach. The findings reveal that his interpretation reflects a remarkable organization in connecting verses and Surahs, affirming its significance as a reference for studying Qur'anic interrelations. This work underscores the importance of this science in unveiling the Qur'anic miracle and encourages further specialized studies.